Radical polymerizable resin composition and cured product thereof

By adding an expanded material and an initiator to the radical polymer resin composition, the shrinkage rate during the polymerization process is controlled, and the problem of significant shrinkage of the radical polymer resin composition during the polymerization process is solved, thereby achieving a hardened resin composition with low shrinkage.

JP7622649B2Active Publication Date: 2025-01-28RESONAC CORP
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2021567432
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-12-26
Filing Date
2020-12-21
Publication Date
2025-01-28
Estimated Expiration
2040-12-21

AI Technical Summary

Technical Problem

The existing radical polymeric resin compositions have significant shrinkage problems during polymerization, resulting in deformation of industrial products, and traditional methods such as the use of polystyrene beads or A-B block copolymers have not completely solved this problem.

Method used

By adding an appropriate amount of expanded material and a radical polymerization initiator to the radical polymerization resin composition, a composition containing a radical polymerization compound, an expanded material, a polymerization initiator and a aggregate is formed. The shrinkage rate is controlled during the polymerization process by using the expanded material to form a hardened resin with a low shrinkage rate.

Benefits of technology

Reducing shrinkage during polymerization is achieved, ensuring that the resin composition does not affect fluidity after hardening, and providing a hardened resin composition with low shrinkage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007622649000006
    Figure 0007622649000006
  • Figure 0007622649000007
    Figure 0007622649000007
  • Figure 0007622649000008
    Figure 0007622649000008
Patent Text Reader

Abstract

By adding an adequate amount of an expansive material to a radically polymerizable resin composition that causes curing shrinkage due to a decrease in the free volume of a liquid component during the curing, the present invention is able to provide a radically polymerizable resin composition which is capable of suppressing shrinkage, while maintaining good strength. A radically polymerizable resin composition according to the present invention contains a radically polymerizable compound (A), an expansive material (B), a radical polymerization initiator (C) and an aggregate (D). The aggregate (D) contains cement. The amount of the aggregate (D) is from 330 parts by mass to 800 parts by mass relative to 100 parts by mass of the radically polymerizable compound (A).
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a radically polymerizable resin composition and a cured product thereof. This application claims priority based on Japanese Patent Application No. 2019-235911, filed on December 26, 2019, the contents of which are incorporated herein by reference. [Background technology]

[0002] When general liquid vinyl monomers are polymerized, a significant amount of shrinkage occurs. This shrinkage causes distortion problems when vinyl monomers are used in industrial products. Therefore, it is industrially very meaningful to create a resin with a small shrinkage rate during polymerization.

[0003] Radically polymerizable resin compositions such as unsaturated polyester resins and vinyl ester resins (epoxy acrylates) also usually shrink during curing. Since "styrene" and "methyl methacrylate" are often used as monomers, which are listed in Table 1 of Non-Patent Document 1, unsaturated polyester resins in general formulations shrink in volume by about 8 to 12%, and vinyl ester resins shrink in volume by about 8 to 10%. This figure is considerably larger than the 3-6% volume shrinkage that is typical for epoxy resins, and has prevented unsaturated polyester resins and vinyl ester resins from being used in industrial applications, or from being used in other industries and applications.

[0004] As a method for solving this problem, Patent Document 1 describes the use of polystyrene beads as a low shrinkage material, which reduces the number of manufacturing steps or shortens the manufacturing time, and enables the production of a low shrinkage unsaturated polyester resin composition having excellent low shrinkage properties, dimensional stability, and surface smoothness.

[0005] Furthermore, Patent Document 2 describes that by blending an AB type block copolymer with an unsaturated polyester resin composition, it is possible to obtain a low-shrinkage unsaturated polyester resin composition that has low shrinkage during curing and can be used to produce a molded product with excellent heat resistance.

[0006] Furthermore, Patent Document 3 describes that by mixing an AB-type block copolymer (vinyl acetate-styrene type) consisting of A and B segments and fine silica particles with an unsaturated polyester resin, it is possible to obtain a low-shrinkage unsaturated polyester resin composition that has a large low-shrinkage effect during molding at room temperature or medium temperature and has high water resistance. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Japanese Patent Application Publication No. 11-315198 [Patent Document 2] Patent No. 2794802 [Patent Document 3] Japanese Patent Application Publication No. 05-222282 [Non-patent literature]

[0008] [Non-Patent Document 1] Endo, Tsuyoshi, Is volume shrinkage during polymerization inevitable?, Polymer, Vol. 27, February issue (1978), pp. 108-111. Summary of the Invention [Problem to be solved by the invention]

[0009] In conventional radical polymerizable resin compositions, in order to create resins with low shrinkage, a single blend of thermoplastic resins such as polystyrene or a block copolymer of two or more types is used. In most cases, these function as "shrinkage prevention materials." Furthermore, these resin compositions are based on the idea of ​​offsetting the thermal expansion of the thermoplastic resin due to heat generation during curing and the curing shrinkage of the unsaturated polyester resin, and their applications have often been limited to applications in which hot molding is performed at medium temperatures or higher, such as sheet molding compounds (SMC) and bulk molding compounds (BMC).

[0010] The present invention has been made in consideration of the above-mentioned conventional situation, and aims to provide a radical polymerizable resin composition having a small shrinkage rate by incorporating an expansion agent instead of a shrinkage prevention agent, which is not limited by the molding method, use temperature, application, etc., and expands at a constant rate as a whole when the resin composition is cured and then stabilizes. Another object of the present invention is to provide a cured product of the radically polymerizable composition that does not lose its fluidity. [Means for solving the problem]

[0011] That is, the present invention is represented by the following [1] to [8].

[0012] [1] A composition comprising a radical polymerizable compound (A), an expanding material (B), a radical polymerization initiator (C), and an aggregate (D), wherein the aggregate (D) contains cement; The amount of the aggregate (D) is 330 parts by mass to 800 parts by mass relative to 100 parts by mass of the radical polymerizable compound (A). A radical polymerizable resin composition comprising: [2] The radical polymerizable resin composition according to [1], wherein the radical polymerizable compound (A) contains a vinyl ester resin and a radical polymerizable unsaturated monomer. [3] The radical polymerizable resin composition according to [1] or [2], wherein the expandable material (B) comprises at least one selected from the group consisting of quicklime and calcium sulfoaluminate. [4] The radical polymerizable resin composition according to any one of [1] to [3], wherein the radical polymerization initiator (C) is a hydroperoxide. [5] The radical polymerizable resin composition according to any one of [1] to [4], further comprising a metal-containing compound (E) and a thiol compound (F). [6] The radical polymerizable resin composition according to any one of [1] to [5], wherein the expanding material (B) is 0.3 parts by mass to 30 parts by mass per 100 parts by mass of the radical polymerizable compound (A). [7] The radical polymerizable resin composition according to any one of [1] to [6], wherein the radical polymerization initiator (C) is 0.1 to 10 parts by mass per 100 parts by mass of the radical polymerizable compound (A). [8] A cured product of the radical polymerizable resin composition according to any one of [1] to [7]. Effect of the Invention

[0013] According to the present invention, by adding an appropriate amount of an expansion agent to a radically polymerizable resin composition that undergoes cure shrinkage due to a decrease in the free volume of the liquid component during curing, it is possible to provide a radically polymerizable resin composition that expands as a whole at a constant rate when the resin composition cures and then stabilizes, without being limited by the molding method, use temperature, application, etc., and thus has a small shrinkage rate. Furthermore, it is possible to provide a cured product of the radically polymerizable composition whose fluidity is not impaired. [Brief description of the drawings]

[0014] [Figure 1] 1 is a graph showing the results of Examples 1 to 4 and Comparative Example 1. [Diagram 2] 1 is a graph showing the results of Example 5 and Comparative Example 2. [Diagram 3] 1 is a graph showing the results of Comparative Examples 7 and 8. [Figure 4] 1 is a graph showing the results of Example 9 and Comparative Example 14. [Diagram 5] 1 is a graph showing the results of Example 1 and Reference Example 1. [Figure 6] 1 is a graph showing the results of Example 6 and Comparative Example 3. [Figure 7] 1 is a graph showing the results of Example 7 and Comparative Example 4. [Figure 8] 1 is a graph showing the results of Example 8 and Comparative Example 5. [Figure 9] 1 is a graph showing the results of Examples 9 to 13. [Figure 10] 1 is a graph showing the results of Examples 1 and 15 and Comparative Examples 10 to 15. [Figure 11] 1 is a graph showing the results of Examples 1 and 16 to 20. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] The present invention will be described in detail below.

[0016] (Radically polymerizable resin composition) The radical polymerizable resin composition of one embodiment of the present invention contains a radical polymerizable compound (A), an expandable material (B), a radical polymerization initiator (C), and an aggregate (D), and the aggregate (D) contains cement.

[0017] <Radically polymerizable compound (A)> The radical polymerizable resin composition of the present invention uses a radical polymerizable compound (A) as a base material. In the present invention, the radical polymerizable compound (A) refers to a compound that has an ethylenically unsaturated group in the molecule and undergoes a polymerization reaction by a radical. Examples of the radically polymerizable compound (A) include vinyl ester resins (epoxy (meth)acrylate resins), unsaturated polyester resins, polyester (meth)acrylate resins, urethane (meth)acrylate resins, (meth)acrylate resins, radically polymerizable unsaturated monomers, and mixtures of the above resins with radically polymerizable unsaturated monomers. Among these, one or more selected from vinyl ester resins, unsaturated polyester resins, and mixtures of these with radically polymerizable unsaturated monomers are preferred. Among these, vinyl ester resins are more preferred. In this specification, "(meth)acrylate" means "acrylate or methacrylate".

[0018] [Vinyl ester resin] As the vinyl ester resin, a resin obtained by reacting an epoxy resin with an unsaturated monobasic acid can be used.

[0019] Examples of the epoxy resin include bisphenol type epoxy resins, biphenyl type epoxy resins, novolac type epoxy resins, trisphenolmethane type epoxy resins, aralkyldiphenol type epoxy resins, naphthalene type epoxy resins, aliphatic type epoxy resins, etc. These may be used alone or in combination of two or more kinds.

[0020] Examples of bisphenol-type epoxy resins include those obtained by reacting a bisphenol with epichlorohydrin and / or methylepichlorohydrin, and those obtained by reacting a glycidyl ether of bisphenol A, a condensate of the bisphenol with epichlorohydrin and / or methylepichlorohydrin. Examples of bisphenols include bisphenol A, bisphenol F, bisphenol S, and tetrabromobisphenol A. Examples of biphenyl-type epoxy resins include those obtained by reacting biphenol with epichlorohydrin and / or methylepichlorohydrin.

[0021] Examples of novolac type epoxy resins include those obtained by reacting phenol novolac or cresol novolac with epichlorohydrin and / or methyl epichlorohydrin. Examples of trisphenolmethane type epoxy resins include those obtained by reacting trisphenolmethane or triscretholmethane with epichlorohydrin and / or methylepichlorohydrin. Examples of aralkyldiphenol type epoxy resins include those obtained by reacting aralkylphenol with epichlorohydrin and / or methylepichlorohydrin.

[0022] Examples of naphthalene-type epoxy resins include those obtained by reacting dihydroxynaphthalene with epichlorohydrin and / or methylepichlorohydrin.

[0023] Examples of the aliphatic epoxy resin include alicyclic epoxy resin, alicyclic diol diglycidyl ether type epoxy resin, aliphatic diol diglycidyl ether type epoxy resin, poly(oxyalkylene) glycol diglycidyl ether type epoxy resin, and the like.

[0024] Examples of alicyclic epoxy resins include alicyclic diepoxy acetal, alicyclic diepoxy adipate, and alicyclic diepoxy carboxylate. Specific examples of alicyclic diol diglycidyl ethers include diglycidyl ethers of alicyclic diols having 3 to 20 carbon atoms (preferably 6 to 12 carbon atoms, more preferably 7 to 10 carbon atoms), such as cyclohexanedimethanol diglycidyl ether, dicyclopentenyl dialcohol diglycidyl ether, diglycidyl ether of hydrogenated bisphenol A, and dihydroxyterpene diglycidyl ether. Of these, a commercially available product of cyclohexanedimethanol diglycidyl ether is "Denacol EX-216L" manufactured by Nagase ChemteX Corporation.

[0025] Specific examples of the aliphatic diol diglycidyl ether include diglycidyl ethers of aliphatic diols having 2 to 20 carbon atoms (preferably 4 to 12 carbon atoms, more preferably 4 to 8 carbon atoms, particularly preferably 4 to 6 carbon atoms), such as 1,6-hexanediol diglycidyl ether, 1,4-butanediol diglycidyl ether, ethylene glycol diglycidyl ether, and propylene glycol diglycidyl ether. Among these, commercially available products of 1,6-hexanediol diglycidyl ether include "Denacol EX-212L" from Nagase ChemteX Corporation, "SR-16H" and "SR-16HL" from Sakamoto Yakuhin Kogyo Co., Ltd., and "Epogosey (registered trademark) HD" from Yokkaichi Synthetic Co., Ltd. In addition, a commercially available product of 1,4-butanediol diglycidyl ether is "Denacol EX-214L" from Nagase ChemteX Corporation.

[0026] Specific examples of poly(oxyalkylene) glycol diglycidyl ethers include diethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, tripropylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, and poly(tetramethylene) glycol diglycidyl ether.

[0027] Preferable examples of the aliphatic epoxy resin include 1,6-hexanediol diglycidyl ether, polyethylene glycol diglycidyl ether, poly(tetramethylene) glycol diglycidyl ether, etc. Among these, those having a number average molecular weight of 150 to 1000 are more preferable.

[0028] The epoxy resin may be a diglycidyl ester such as dimer acid diglycidyl ester or hexahydrophthalic acid diglycidyl ester. The epoxy resin may be an epoxy resin having an oxazolidone ring obtained by reacting the epoxy resin with a diisocyanate. A specific example of the epoxy resin having an oxazolidone ring is Araldite (registered trademark) AER4152 manufactured by Asahi Kasei Epoxy.

[0029] The unsaturated monobasic acid may be a known one, such as (meth)acrylic acid, crotonic acid, cinnamic acid, etc. Also, a reaction product of a compound having one hydroxyl group and one or more (meth)acryloyl groups with a polybasic acid anhydride may be used. In this specification, "(meth)acrylic acid" means one or both of "acrylic acid and methacrylic acid", and "(meth)acryloyl group" means one or both of "acryloyl group and methacryloyl group". The polybasic acid is used to increase the molecular weight of the epoxy resin, and known polybasic acids can be used. Examples include succinic acid, glutaric acid, adipic acid, sebacic acid, phthalic acid, fumaric acid, maleic acid, itaconic acid, tetrahydrophthalic acid, hexahydrophthalic acid, dimer acid, ethylene glycol 2 moles maleic anhydride adduct, polyethylene glycol 2 moles maleic anhydride adduct, propylene glycol 2 moles maleic anhydride adduct, polypropylene glycol 2 moles maleic anhydride adduct, dodecanedioic acid, tridecanedioic acid, octadecanedioic acid, 1,16-(6-ethylhexadecane)dicarboxylic acid, 1,12-(6-ethyldodecane)dicarboxylic acid, carboxyl group-terminated butadiene-acrylonitrile copolymer (trade name: Hycar CTBN), etc.

[0030] [Unsaturated polyester resin] As the unsaturated polyester resin, a resin obtained by subjecting a dibasic acid component containing an unsaturated dibasic acid and, if necessary, a saturated dibasic acid, to an esterification reaction with a polyhydric alcohol component can be used. Examples of the unsaturated dibasic acid include maleic acid, maleic anhydride, fumaric acid, itaconic acid, itaconic anhydride, etc., which may be used alone or in combination of two or more kinds. Examples of the saturated dibasic acid include aliphatic dibasic acids such as adipic acid, suberic acid, azelaic acid, sebacic acid, and isosebacic acid; aromatic dibasic acids such as phthalic acid, phthalic anhydride, halogenated phthalic anhydride, isophthalic acid, terephthalic acid, tetrachlorophthalic acid, tetrachlorophthalic anhydride, dimer acid, 2,6-naphthalenedicarboxylic acid, 2,7-naphthalenedicarboxylic acid, 2,3-naphthalenedicarboxylic acid, 2,3-naphthalenedicarboxylic acid anhydride, 4,4′-biphenyldicarboxylic acid, and dialkyl esters thereof; and halogenated saturated dibasic acids. These may be used alone or in combination of two or more.

[0031] The polyhydric alcohol is not particularly limited, and examples thereof include ethylene glycol, propylene glycol, diethylene glycol, dipropylene glycol, 1,2-butanediol, 1,3-butanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, neopentyl glycol, 2-methyl-1,3-propanediol, 2-methyl-1,4-butanediol, 2,2-dimethyl-1,3-propanediol, 2,2,4-trimethyl-1,3-pentanediol, 2-ethyl-2- dihydric alcohols such as butyl-1,3-propanediol, 3-methyl-1,5-pentanediol, diethylene glycol, triethylene glycol, polyethylene glycol, dipropylene glycol, polypropylene glycol, 1,2-cyclohexane glycol, 1,3-cyclohexane glycol, 1,4-cyclohexane glycol, 1,4-cyclohexanedimethanol, paraxylene glycol, bicyclohexyl-4,4'-diol, 2,6-decalin glycol, and 2,7-decalin glycol; dihydric alcohols such as adducts of dihydric phenols such as hydrogenated bisphenol A, cyclohexanedimethanol, bisphenol A, bisphenol F, bisphenol S, and tetrabromobisphenol A with alkylene oxides such as propylene oxide or ethylene oxide; Examples of the alcohol include trihydric or higher alcohols such as 1,2,3,4-tetrahydroxybutane, glycerin, trimethylolpropane, and pentaerythritol.

[0032] The unsaturated polyester may be modified with a dicyclopentadiene compound within the scope of the present invention. The modification method with a dicyclopentadiene compound may include a known method in which, for example, an addition product of dicyclopentadiene and maleic acid (cydecanol monomaleate) is obtained, and then the product is used as a monobasic acid to introduce a dicyclopentadiene skeleton. An oxidative polymerization (air curing) group such as an allyl group or a benzyl group can be introduced into the vinyl ester resin or unsaturated polyester resin used in the present invention. There is no particular limitation on the method of introduction, but examples include the addition of a polymer containing an oxidative polymerization group, condensation of a compound having a hydroxyl group and an allyl ether group, and a method of adding a reaction product of a compound having a hydroxyl group and an allyl ether group and an acid anhydride to allyl glycidyl ether or 2,6-diglycidyl phenyl allyl ether. In the present invention, oxidative polymerization (air curing) refers to crosslinking that occurs with the generation and decomposition of peroxide due to the oxidation of a methylene bond between an ether bond and a double bond, as seen in, for example, an allyl ether group.

[0033] [Polyester (meth)acrylate resin, urethane (meth)acrylate resin, and (meth)acrylate resin] The polyester (meth)acrylate resin in the present invention may be, for example, a polyester obtained by reacting a polyvalent carboxylic acid with a polyhydric alcohol, specifically, a resin obtained by reacting (meth)acrylic acid with hydroxyl groups at both ends of polyethylene terephthalate or the like. Furthermore, as the urethane (meth)acrylate resin, for example, a resin obtained by reacting (meth)acrylic acid with hydroxyl groups or isocyanato groups at both ends of polyurethane obtained by reacting isocyanate with polyhydric alcohol can be used. Examples of the (meth)acrylate resin that can be used include poly(meth)acrylic resins having one or more substituents selected from a hydroxyl group, an isocyanato group, a carboxyl group, and an epoxy group, and resins obtained by reacting a (meth)acrylic acid ester having a hydroxyl group with a substituent of a polymer of a monomer having the above substituent and a (meth)acrylate.

[0034] [Radically polymerizable unsaturated monomer] In the present invention, a radically polymerizable unsaturated monomer can be used as the radically polymerizable compound (A). The radical polymerizable unsaturated monomer may be used alone, but it is preferable to use the radical polymerizable unsaturated monomer as a mixture with at least one of the vinyl ester resin and the unsaturated polyester resin. The radically polymerizable unsaturated monomer is not particularly limited, but is preferably one having a vinyl group or a (meth)acryloyl group. Specific examples of monomers having a vinyl group include styrene, p-chlorostyrene, vinyltoluene, α-methylstyrene, dichlorostyrene, divinylbenzene, tert-butylstyrene, vinyl acetate, diallyl phthalate, and triallyl isocyanurate.

[0035] Specific examples of monomers having a (meth)acryloyl group include (meth)acrylic acid esters, etc. Specifically, methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, iso-butyl (meth)acrylate, tert-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, cyclohexyl (meth)acrylate, benzyl (meth)acrylate, stearyl (meth)acrylate, tridecyl (meth)acrylate, cyclohexyl (meth)acrylate, dicyclopentanyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, phenoxyethyl methacrylate, 2-hydroxyethyl methacrylate, ethylene glycol monomethyl ether (meth)acrylate, ethylene glycol monoethyl ether (meth)acrylate, ethylene glycol monobutyl ether (meth)acrylate, ethylene glycol monohexyl ... ) acrylate, ethylene glycol mono 2-ethylhexyl ether (meth)acrylate, diethylene glycol monomethyl ether (meth)acrylate, diethylene glycol monoethyl ether (meth)acrylate, diethylene glycol monobutyl ether (meth)acrylate, diethylene glycol monohexyl ether (meth)acrylate, diethylene glycol mono 2-ethylhexyl ether (meth)acrylate, neopentyl glycol di(meth)acrylate, PTMG dimethacrylate, 1,3-butylene glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 2-hydroxy-1,3-dimethacryloxypropane, 2,2-bis[4-(methacryloylethoxy)phenyl]propane, 2,2-bis[4-(methacryloxy-diethoxy)phenyl]propane, 2,Examples of the acrylates include 2-bis[4-(methacryloxy-polyethoxy)phenyl]propane, tetraethylene glycol diacrylate, bisphenol A EO-modified (n=2) diacrylate, isocyanuric acid EO-modified (n=3) diacrylate, pentaerythritol diacrylate monostearate, dicyclopentenyl acrylate, dicyclopentenyloxyethyl acrylate, tricyclodecanyl (meth)acrylate, and tris(2-hydroxyethyl)isocyanuracrylate.

[0036] Further, examples of polyfunctional (meth)acrylic acid esters include alkanediol di(meth)acrylates such as ethylene glycol di(meth)acrylate, 1,2-propylene glycol di(meth)acrylate, 1,3-butylene glycol di(meth)acrylate, 1,4-butylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, and 1,6-hexanediol di(meth)acrylate; diethylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, and triethylene glycol (meth)acrylate. polyoxyalkylene glycol di(meth)acrylates such as tetraethylene glycol di(meth)acrylate and polyethylene glycol (meth)acrylate; trimethylolpropane di(meth)acrylate, glycerin di(meth)acrylate, pentaerythritol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, glycerin tri(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, and dipentaerythritol hexa(meth)acrylate.

[0037] Furthermore, the following compounds can also be used as the radical polymerizable unsaturated monomer.Specific examples include divinylbenzene, diallyl phthalate, triallyl phthalate, triallyl cyanurate, triallyl isocyanurate, allyl (meth)acrylate, diallyl fumarate, allyl methacrylate, vinylbenzyl butyl ether, vinylbenzyl hexyl ether, vinylbenzyl octyl ether, vinylbenzyl (2-ethylhexyl) ether, vinylbenzyl (β-methoxymethyl) ether, vinylbenzyl (n-butoxypropyl) ether, vinylbenzyl cyclohexyl ether, vinylbenzyl (β-phenoxyethyl) ether, vinylbenzyl dicyclopentenyl ether, vinylbenzyl dicyclopentenyloxyethyl ether, vinylbenzyl dicyclopentenyl methyl ether, and divinylbenzyl ether. In addition to the above, dicyclopentenyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate and the like can also be used. These may be used alone or in combination of two or more.

[0038] The radical polymerizable unsaturated monomer can be used to reduce the viscosity of the radical polymerizable resin composition of the present invention and improve hardness, strength, chemical resistance, water resistance, etc., but if the content is too high, it may lead to deterioration of the cured product or environmental pollution. Therefore, the content of the radical polymerizable unsaturated monomer in the radical polymerizable compound (A) is preferably 90 mass% or less.

[0039] The radical polymerizable compound (A) may contain residual catalysts and polymerization inhibitors used in synthesizing vinyl ester resins, unsaturated polyester resins, polyester (meth)acrylate resins, urethane (meth)acrylate resins, and (meth)acrylate resins. Examples of catalysts include compounds containing tertiary nitrogen, such as triethylamine, pyridine derivatives, and imidazole derivatives; amine salts, such as tetramethylammonium chloride and triethylamine; and phosphorus compounds, such as trimethylphosphine and triphenylphosphine. Examples of the polymerization inhibitor include hydroquinone, methylhydroquinone, and phenothiazine. When the catalyst or polymerization inhibitor remains in the radically polymerizable compound (A), the amount thereof is preferably 0.001 to 2 parts by mass, respectively, per 100 parts by mass of the vinyl ester resin and the unsaturated polyester resin in total.

[0040] The content of the radical polymerizable compound (A) in the radical polymerizable resin composition of the present invention is preferably 5 to 99.9 mass%, more preferably 10 to 80 mass%, further preferably 15 to 60 mass%, and further preferably 18 to 40 mass%. When the content of the radical polymerizable compound (A) in the radical polymerizable resin composition is within the above range, the hardness of the cured product is further improved.

[0041] <Expansion material (B)> The expansive material (B) used in the present invention may be any expansive material that satisfies the standard of Japanese Industrial Standard JIS A 6202 "Expansive material for concrete" and is generally used as an expansive material for concrete. Specifically, any expansive material that produces calcium hydroxide or ettringite by hydration reaction is acceptable. For example, an expansive material (B) containing at least one selected from the group consisting of quicklime and calcium sulfoaluminate is preferred. More preferred expansive materials include (1) expansive materials containing quicklime as an active ingredient (quicklime-based expansive materials), (2) expansive materials containing calcium sulfoaluminate as an active ingredient (ettringite-based expansive materials), and (3) expansive materials containing quicklime-ettringite composite systems.

[0042] Specific examples of quicklime-based expansive materials include Pacific Hyper Expan-K, Pacific Hyper Expan-M, Pacific Expan-K, Pacific Expan-M, and Pacific N-EX, manufactured by Pacific Materials. Specific examples of ettringite-based expanding materials include Denka CSA #10 and Denka CSA #20 manufactured by Denka. Specific examples of quicklime-ettringite composite expanding materials include Denka Power CSA Type S, Denka Power CSA Type R, and Denka Power CSA Type T manufactured by Denka.

[0043] The content of the expanding material (B) of the present invention is preferably 0.3 to 30 parts by mass, more preferably 0.5 to 25 parts by mass, even more preferably 0.7 to 20 parts by mass, and most preferably 1 to 16 parts by mass, relative to 100 parts by mass of the radical polymerizable compound (A). If the content of the expanding material (B) is 30 parts by mass or less, the expansion coefficient does not exceed the elongation amount of the resin when the radical polymerizable resin composition is cured. On the other hand, if the content is 0.3 parts by mass or more, the expansion performance for the radical polymerizable compound (A) is not not expressed. In addition, these expanding materials (B) may be used alone or in a mixture of two or more kinds.

[0044] <Radical polymerization initiator (C)> The radical polymerizable resin composition of the present invention contains a radical polymerization initiator (C) as a curing agent. The radical polymerization initiator (C) may be a thermal radical polymerization initiator (C1) or a photoradical polymerization initiator (C2). Among them, the thermal radical polymerization initiator (C1) is preferred. Examples of the thermal radical polymerization initiator (C1) include diacyl peroxides such as benzoyl peroxide, peroxyesters such as tert-butyl peroxybenzoate, hydroperoxides (RCOOH, Hydroperoxides) such as cumene hydroperoxide (CHP), diisopropylbenzene hydroperoxide, tert-butyl hydroperoxide, and paramenthane hydroperoxide, dialkyl peroxides such as dicumyl peroxide, ketone peroxides such as methyl ethyl ketone peroxide and acetylacetone peroxide, peroxyketals, alkyl peresters, and organic peroxides such as percarbonates. Among these, hydroperoxide radical polymerization initiators (RCOOH) (also simply referred to as hydroperoxides) are preferred, and cumene hydroperoxides (CHP) such as Percumyl (registered trademark) H-80 manufactured by NOF Corp., and diisopropylbenzene hydroperoxides such as Percumyl (registered trademark) P manufactured by NOF Corp. are more preferred.

[0045] Examples of the photoradical polymerization initiator (C2) include benzoin ether-based initiators such as benzoin alkyl ether; benzophenone-based initiators such as benzophenone, benzil, and methyl orthobenzoyl benzoate; acetophenone-based initiators such as benzil dimethyl ketal, 2,2-diethoxyacetophenone, 2-hydroxy-2-methylpropiophenone, 4-isopropyl-2-hydroxy-2-methylpropiophenone, and 1,1-dichloroacetophenone; and thioxanthone-based initiators such as 2-chlorothioxanthone, 2-methylthioxanthone, and 2-isopropylthioxanthone.

[0046] Examples of the photoradical polymerization initiator (C2) having sensitivity from ultraviolet light to the visible light region include known initiators such as acetophenone-based, benzyl ketal-based, and (bis)acylphosphine oxide-based initiators. Specific examples include Irgacure-1700 (Ciba Specialty Chemicals, Inc.), which is a mixture of 2-hydroxy-2-methyl-1-phenylpropan-1-one (trade name: Darocur 1173, manufactured by Ciba Specialty Chemicals, Inc.) and bis(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide (manufactured by Ciba Specialty Chemicals, Inc.) in a ratio of 75% / 25%; 1-hydroxycyclohexyl phenyl Ketone (product name: Irgacure 184, manufactured by Chiba Specialty Chemicals Co., Ltd.) and bis(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide (product name: Irgacure 1800, manufactured by Chiba Specialty Chemicals Co., Ltd.) were mixed in a ratio of 75% / 25% to produce Irgacure 1800 (manufactured by Chiba Specialty Chemicals Co., Ltd.), and bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide (product name: Irgacure 819, manufactured by Chiba Specialty Chemicals Co., Ltd.) were mixed in a ratio of 50% / 50% to produce Irgacure 1850 (manufactured by Chiba Specialty Chemicals Co., Ltd.); bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide (product name: Irgacure 819, manufactured by Chiba Specialty Chemicals Co., Ltd.); 2,4,6-trimethylbenzoyldiphenylphosphine oxide (product name: Lucirin TPO, manufactured by BASF Ltd.); Darocur 4265, which is a 50% / 50% mixture of 2-hydroxy-2-methyl-1-phenylpropan-1-one (trade name: Darocur 1173, manufactured by Chiba Specialty Chemicals Co., Ltd.) and 2,4,6-trimethylbenzoyldiphenylphosphine oxide (trade name: Lucirin TPO, manufactured by BASF Ltd.).

[0047] Examples of the photoradical polymerization initiator (C2) having photosensitivity in the visible light region include camphorquinone, benzyltrimethylbenzoyldiphenylphosphinoxide, methylthioxanthone, and dicyclopentadiethyltitanium-di(pentafluorophenyl). These radical polymerization initiators (C) may be used alone or in combination of two or more. In order to support the main reaction of the heat curing or photocuring, the other reaction may be introduced, and the heat radical polymerization initiator (C1) and the photoradical polymerization initiator (C2) may be used in combination as necessary.

[0048] In addition, depending on the molding conditions, they can also be used in composite forms such as organic peroxide / dye system, diphenyl iodide salt / dye system, imidazole / keto compound, hexaarylbiimidazole compound / hydrogen donor compound, mercaptobenzothiazole / thiopyrylium salt, metal arene / cyanine dye, and hexaarylbiimidazole / radical generator.

[0049] When the radical polymerizable resin composition of the present invention contains a radical polymerization initiator (C), the amount thereof is preferably 0.1 to 10 parts by mass, more preferably 0.2 to 8.0 parts by mass, even more preferably 0.3 to 6.0 parts by mass, and most preferably 0.3 to 5.0 parts by mass, relative to 100 parts by mass of the radical polymerizable compound (A).

[0050] <Aggregate (D)> The radical polymerizable resin composition of the present invention includes aggregate (D) containing cement. The aggregate (D) other than cement is not particularly limited, and can be used in mortar or concrete. The aggregate other than cement is not particularly limited, and can be, for example, calcium carbonate, crushed stone, sandstone, kansui stone, marble, quartz, limestone, silica sand, silica stone, river sand, etc. In addition, from the viewpoint of weight reduction, lightweight aggregates such as sintered shale, silica balloon, non-silica balloon perlite can also be used. Among these, silica sand is preferred, and silica sand No. 7 and silica sand No. 8 are more preferred.

[0051] As the cement, Portland cement, other mixed cements, ultra-fast hardening cements, etc. can be used without any particular restrictions. As the Portland cement, various Portland cements such as low heat, moderate heat, normal, early strength, ultra early strength, and sulfate resistant Portland cements can be mentioned. As the mixed cements, blast furnace cement, fly ash cement, silica cement, etc. can be mentioned. Among these, inexpensive Portland cement is preferable, and early strength and ultra early strength Portland cements are more preferable. As for these cements, the above-mentioned cements can be used alone or in any combination at any mixing ratio.

[0052] Calcium carbonate functions as an extender pigment in the coating film, being transparent and not hiding the coated surface (substrate surface), and has the effect of filling recesses, reducing paint costs, etc. An example of this calcium carbonate on the market is TM-2 (manufactured by Yukou Mining Co., Ltd.). Calcium carbonate has a specific particle size distribution, is highly dispersible, and is porous, so that it can reduce the specific gravity of the aggregate itself, making it less likely to sag, and improve film-forming properties.

[0053] Examples of silicate-based balloons include shirasu balloons, perlite, glass (silica) balloons, and fly ash balloons. Examples of non-silica-based balloons include alumina balloons, zirconia balloons, and carbon balloons. Specific examples of perlite include Perlite FL-0 (trade name, manufactured by Fuyo Perlite Co., Ltd.), Hardlite B-03, Hardlite B-04, and Hardlite B-05 (all trade names, manufactured by Showa Chemical Industry Co., Ltd.).

[0054] The content of the aggregate (D) in the composition of the present invention is not particularly limited, but is 330 to 800 parts by mass, preferably 350 to 800 parts by mass, and more preferably 370 to 450 parts by mass, relative to 100 parts by mass of the radical polymerizable compound (A). In particular, if the content of the aggregate is 330 parts by mass or more, practical fluidity can be ensured. Also, if the content of the aggregate is 800 parts by mass or less, the amount of adhesion to the trowel is reduced, and a decrease in workability can be prevented. The content of cement in aggregate (D) is not particularly limited, but is preferably 1 to 80 parts by mass, more preferably 5 to 50 parts by mass, and even more preferably 5 to 30 parts by mass, per 100 parts by mass of aggregate (D). In particular, if the content of cement is 1 part by mass or more, the particle size distribution of the aggregate can be optimized and practical fluidity can be ensured. Also, if the content of cement is 80 parts by mass or less, stickiness due to deterioration of fluidity can be prevented.

[0055] <Metal-containing compounds (E)> The radical polymerizable resin composition of the present invention can use one or more metal-containing compounds (E) selected from metal soaps (E1) and metal complexes (E2) having a β-diketone skeleton as a curing accelerator. The metal soap (E1) in the present invention refers to a salt of a long-chain fatty acid or an organic acid other than a long-chain fatty acid with a metal element other than potassium and sodium. The metal complex (E2) having a β-diketone skeleton in the present invention refers to a complex in which a compound having a structure in which one carbon atom is between two carbonyl groups is coordinated to a metal element.

[0056] The content of the metal-containing compound (E) in the radical polymerizable resin composition in terms of the metal component is preferably 0.0001 to 5 parts by mass, more preferably 0.001 to 4 parts by mass, and even more preferably 0.005 to 3 parts by mass, relative to 100 parts by mass of the radical polymerizable compound (A) described above. When the content of the metal-containing compound (E) in terms of the metal component is within the above range, curing proceeds quickly even in water and in a humid atmosphere.

[0057] [Metal soap (E1)] The long-chain fatty acid in the metal soap (E1) is not particularly limited, but is preferably, for example, a fatty acid having 6 to 30 carbon atoms. Specifically, preferred are linear or cyclic saturated fatty acids such as octanoic acids such as heptanoic acid and 2-ethylhexanoic acid, nonanoic acid, decanoic acid, neodecanoic acid, undecanoic acid, dodecanoic acid, tetradecanoic acid, hexadecanoic acid, octadecanoic acid, eicosanoic acid, docosanoic acid, tetracosanoic acid, hexacosanoic acid, octacosanoic acid, triacontanoic acid, and naphthenic acid, and unsaturated fatty acids such as oleic acid, linoleic acid, and linolenic acid. Other examples include rosin acid, linseed oil fatty acid, soybean oil fatty acid, tall oil acid, and the like.

[0058] The organic acid other than the long-chain fatty acid in the metal soap (E1) is not particularly limited, but is preferably a weak acid compound having a carboxy group, a hydroxy group, or an enol group, which is soluble in an organic solvent. Examples of compounds having a carboxy group include carboxylic acids such as formic acid, acetic acid, and oxalic acid; hydroxy acids such as citric acid, bile acid, sugar acid, 12-hydroxystearic acid, hydroxycinnamic acid, and folic acid; amino acids such as alanine and arginine; and aromatic acids such as benzoic acid and phthalic acid. Examples of compounds having a hydroxy group or an enol group include ascorbic acid, alpha acid, imido acid, erythorbic acid, croconic acid, kojic acid, squaric acid, sulfinic acid, teichoic acid, dehydroacetic acid, delta acid, uric acid, hydroxamic acid, humic acid, fulvic acid, and phosphonic acid. Among these, long-chain fatty acids are preferred, linear or cyclic saturated fatty acids having 6 to 16 carbon atoms, or unsaturated fatty acids having 6 to 16 carbon atoms are more preferred, octanoic acid, 2-ethylhexanoic acid, and naphthenic acid are even more preferred, and 2-ethylhexanoic acid and naphthenic acid are even more preferred.

[0059] Examples of the metal element constituting the metal soap (E1) include metal elements of Groups 1 and 2 such as lithium, magnesium, calcium, and barium (excluding potassium and sodium), metal elements of Groups 3 to 12 such as titanium, zirconium, vanadium, manganese, iron, ruthenium, cobalt, rhodium, nickel, palladium, platinum, copper, silver, gold, and zinc, metal elements of Groups 13 and 14 such as aluminum, indium, tin, and lead, rare earth metal elements such as neodymium and cerium, and bismuth. In the present invention, metal elements of Groups 2 to 12 are preferred, zirconium, barium, vanadium, manganese, iron, cobalt, copper, titanium, bismuth, calcium, lead, tin and zinc are more preferred, zirconium, manganese, iron, cobalt, copper, titanium, bismuth, calcium, lead, tin and zinc are even more preferred, and zirconium, manganese, cobalt, bismuth and calcium are even more preferred.

[0060] Specific examples of the metal soap (E1) include zirconium octylate, manganese octylate, cobalt octylate, bismuth octylate, calcium octylate, zinc octylate, vanadium octylate, lead octylate, tin octylate, cobalt naphthenate, copper naphthenate, barium naphthenate, bismuth naphthenate, calcium naphthenate, lead naphthenate, and tin naphthenate, and among these, zirconium octylate, manganese octylate, cobalt octylate, bismuth octylate, calcium octylate, lead octylate, tin octylate, bismuth naphthenate, calcium naphthenate, lead naphthenate, and tin naphthenate are more preferred. Among these, manganese octylate and cobalt octylate are particularly preferred. A specific example of cobalt octylate is cobalt hexoate (cobalt content in the total product: 8% by mass, molecular weight: 345.34) manufactured by Toei Kako Co., Ltd. A specific example of manganese octylate is manganese hexoate (manganese content in the total product: 8% by mass, molecular weight: 341.35) manufactured by Toei Kako Co., Ltd.

[0061] [Metal complexes with β-diketone skeletons (E2)] Metal complex (E2) having a β-diketone skeleton (hereinafter also referred to as "metal complex (E2)"). Examples of the metal complex (E2) include complexes formed between acetylacetone, ethyl acetoacetate, benzoylacetone, etc. and a metal. These metal complexes (E2) also exhibit the same functions as the metal soap (E1). Examples of the metal element constituting the metal complex (E2) include the same metal elements as those in the metal soap (E1).

[0062] Specific examples of the metal complex (E2) include zirconium acetylacetonate, vanadium acetylacetonate, cobalt acetylacetonate, titanium acetylacetonate, titanium dibutoxybis(acetylacetonate), iron acetylacetonate, and cobalt ethyl acetoacetate. Among these, zirconium acetylacetonate, titanium acetylacetonate, and titanium dibutoxybis(acetylacetonate) are more preferable.

[0063] <Thiol Compound (F)> The radical polymerizable resin composition of the present invention may contain one or more thiol compounds (F) selected from a secondary thiol compound (F-1) and a tertiary thiol compound (F-2). In the present invention, the thiol compound (F) functions as a curing accelerator and is presumed to coordinate in the vicinity of the metal of the metal-containing compound (E) to prevent the deactivation of the metal by water. The thiol compound (F) used in the present invention is not particularly limited as long as it has one or more mercapto groups (hereinafter, each may be referred to as a "secondary mercapto group" and a "tertiary mercapto group") bonded to a secondary or tertiary carbon atom in the molecule, but from the viewpoint of rapidly proceeding with curing even in water and from the viewpoint of preventing the metal of the metal-containing compound (E) from being deactivated by water, a polyfunctional thiol, which is a compound having two or more secondary or tertiary mercapto groups in the molecule, is preferred, and among them, a bifunctional thiol, which is a compound having two secondary or tertiary mercapto groups in the molecule, is preferred. In addition, the secondary thiol compound (F-1) is more preferred than the tertiary thiol compound (F-2). As used herein, "polyfunctional thiol" refers to a thiol compound having two or more mercapto groups as functional groups, and "bifunctional thiol" refers to a thiol compound having two mercapto groups as functional groups.

[0064] The compound having two or more secondary or tertiary mercapto groups in the molecule is not particularly limited, but for example, a compound having at least one structure represented by the following formula (Q) and having two or more secondary or tertiary mercapto groups in the molecule including the mercapto group in the structure represented by the following formula (Q) is preferred.

[0065] [ka]

[0066] (In formula (Q), R 1 is a hydrogen atom, an alkyl group having 1 to 10 carbon atoms, or an aromatic group having 6 to 18 carbon atoms; R 2 is an alkyl group having 1 to 10 carbon atoms or an aromatic group having 6 to 18 carbon atoms, and * indicates that it is linked to an arbitrary organic group. a is an integer of 0 to 2.)

[0067] [Secondary thiol compound (F-1)] When the thiol compound (F) having the structure represented by the formula (Q) is a secondary thiol compound (F-1), specific examples thereof include 3-mercaptobutyric acid, di(1-mercaptoethyl) 3-mercaptophthalate, di(2-mercaptopropyl) phthalate, di(3-mercaptobutyl) phthalate, ethylene glycol bis(3-mercaptobutyrate), propylene glycol bis(3-mercaptobutyrate), diethylene glycol bis(3-mercaptobutyrate), butanediol bis(3-mercaptobutyrate), octanediol bis(3-mercaptobutyrate), and the like. mercaptobutyrate), trimethylolethane tris(3-mercaptobutyrate), trimethylolpropane tris(3-mercaptobutyrate), pentaerythritol tetrakis(3-mercaptobutyrate), dipentaerythritol hexakis(3-mercaptobutyrate), ethylene glycol bis(2-mercaptopropionate), propylene glycol bis(2-mercaptopropionate), diethylene glycol bis(2-mercaptopropionate), butanediol bis(2-mercaptopropionate), octanedio ethanol bis(2-mercaptopropionate), trimethylolpropane tris(2-mercaptopropionate), pentaerythritol tetrakis(2-mercaptopropionate), dipentaerythritol hexakis(2-mercaptopropionate), ethylene glycol bis(4-mercaptovalerate), diethylene glycol bis(4-mercaptovalerate), butanediol bis(4-mercaptovalerate), octanediol bis(4-mercaptovalerate), trimethylolpropane tris(4-mercaptovalerate), Pentaerythritol tetrakis(4-mercaptovalerate), dipentaerythritol hexakis(4-mercaptovalerate), ethylene glycol bis(3-mercaptovalerate), propylene glycol bis(3-mercaptovalerate), diethylene glycol bis(3-mercaptovalerate), butanediol bis(3-mercaptovalerate), octanediol bis(3-mercaptovalerate), trimethylolpropane tris(3-mercaptovalerate), pentaerythritol tetrakis(3-mercaptovalerate),Dipentaerythritol hexakis(3-mercaptovalerate), hydrogenated bisphenol A bis(3-mercaptobutyrate), bisphenol A dihydroxyethyl ether-3-mercaptobutyrate, 4,4'-(9-fluorenylidene)bis(2-phenoxyethyl(3-mercaptobutyrate)), ethylene glycol bis(3-mercapto-3-phenylpropionate), propylene glycol bis(3-mercapto-3-phenylpropionate), diethylene glycol bis(3-mercapto-3-phenylpropionate), lopionate), butanediol bis(3-mercapto-3-phenylpropionate), octanediol bis(3-mercapto-3-phenylpropionate), trimethylolpropane tris(3-mercapto-3-phenylpropionate), tris-2-(3-mercapto-3-phenylpropionate)ethyl isocyanurate, pentaerythritol tetrakis(3-mercapto-3-phenylpropionate), dipentaerythritol hexakis(3-mercapto-3-phenylpropionate), etc.

[0068] Among the secondary thiol compounds (F-1), commercially available compounds having two or more secondary mercapto groups in the molecule include 1,4-bis(3-mercaptobutyryloxy)butane (manufactured by Showa Denko K.K., KarenzMT (registered trademark) BD1), pentaerythritol tetrakis(3-mercaptobutyrate) (manufactured by Showa Denko K.K., KarenzMT (registered trademark) PE1), 1,3,5-tris[2-(3-mercaptobutyryloxyethyl)]-1,3,5-triazine-2,4,6(1H,3H,5H)-trione (manufactured by Showa Denko K.K., KarenzMT (registered trademark) NR1), trimethylolethane tris(3-mercaptobutyrate) (manufactured by Showa Denko K.K., TEMB), and trimethylolpropane tris(3-mercaptobutyrate) (manufactured by Showa Denko K.K., TPMB), and it is preferable to use one or more of these. Among these, 1,4-bis(3-mercaptobutyryloxy)butane (KarenzMT (registered trademark) BD1, manufactured by Showa Denko KK) is preferable.

[0069] [Tertiary thiol compound (F-2)] When the thiol compound (F) having a structure represented by the formula (Q) is a tertiary thiol compound (F-2), specific examples thereof include di(2-mercaptoisobutyl)phthalate, ethylene glycol bis(2-mercaptoisobutyrate), propylene glycol bis(2-mercaptoisobutyrate), diethylene glycol bis(2-mercaptoisobutyrate), butanediol bis(2-mercaptoisobutyrate), octanediol bis(2-mercaptoisobutyrate), trimethylolethane tris(2-mercaptoisobutyrate), trimethylolpropane tris(2-mercaptoisobutyrate), pentaerythritol tetrakis(2-mercaptoisobutyrate), dipentaerythritol hexakis(2-mercaptoisobutyrate), and the like. butylate), di(3-mercapto-3-methylbutyl)phthalate, ethylene glycol bis(3-mercapto-3-methylbutyrate), propylene glycol bis(3-mercapto-3-methylbutyrate), diethylene glycol bis(3-mercapto-3-methylbutyrate), butanediol bis(3-mercapto-3-methylbutyrate), octanediol bis(3-mercapto-3-methylbutyrate), trimethylolethane tris(3-mercapto-3-methylbutyrate), trimethylolpropane tris(3-mercapto-3-methylbutyrate), pentaerythritol tetrakis(3-mercapto-3-methylbutyrate), dipentaerythritol hexakis(3-mercapto-3-methylbutyrate), and the like.

[0070] The total amount of the thiol compound (F) in the radical polymerizable resin composition of the present invention is preferably 0.01 to 10 parts by mass, more preferably 0.1 to 7 parts by mass, even more preferably 0.1 to 5 parts by mass, and even more preferably 0.2 to 4 parts by mass, based on 100 parts by mass of the radical polymerizable compound (A) described above. When the amount of the thiol compound (F) is 0.01 parts by mass or more, a sufficient curing function can be obtained, and when it is 10 parts by mass or less, curing proceeds quickly.

[0071] The total molar ratio [(F) / (E)] of the thiol compound (F) to the metal component of the metal-containing compound (E) is preferably 0.1 to 15, and in one embodiment of the present invention, more preferably 0.3 to 10, even more preferably 0.6 to 8, and even more preferably 0.8 to 5, and in another embodiment of the present invention, more preferably 0.5 to 15, even more preferably 1 to 12, even more preferably 1.5 to 10, and even more preferably 2 to 9. When the molar ratio [(F) / (E)] is 0.1 or more, the thiol compound (F) can be sufficiently coordinated in the vicinity of the metal of the metal-containing compound (E), and by setting the molar ratio to 15 or less, the balance between production cost and effect is improved.

[0072] The thiol compound (F) may be used alone or in combination of two or more. When the secondary thiol compound (F-1) and the tertiary thiol compound (F-2) are used in combination, the molar ratio [(F-1) / (F-2)] of the two is preferably 0.001 to 1000, more preferably 1 to 10. When the molar ratio [(F-1) / (F-2)] is within the above range, the metal-containing compound (A) and the thiol compound (F) are stable in the radical polymerizable resin composition, and disulfide compounds caused by bonds between the thiol compounds (F) as by-products are not generated. From the viewpoint of storing the radical polymerizable resin composition with the metal-containing compound (E) and the thiol compound (F) in a stable state, it is preferable to use the secondary thiol compound (F-1) or the tertiary thiol compound (F-2) alone.

[0073] <Curing accelerator (G)> The radically polymerizable resin composition of the present invention may contain a curing accelerator (G) other than the metal-containing compound (E) and the thiol compound (F) for the purpose of improving the curability. Examples of the curing accelerator (G) other than the metal-containing compound (E) and the thiol compound (F) include amines, specifically, aniline, N,N-dimethylaniline, N,N-diethylaniline, p-toluidine, N,N-dimethyl-p-toluidine, N,N-bis(2-hydroxyethyl)-p-toluidine, 4-(N,N-dimethylamino)benzaldehyde, 4-[N,N-bis(2-hydroxyethyl)amino]benzaldehyde, 4-(N-methyl-N-hydroxyphenyl)-2-phenylpropanediol ... Examples of the amines that can be used include N,N-substituted anilines such as N,N-bis(hydroxyethylamino)benzaldehyde, N,N-bis(2-hydroxypropyl)-p-toluidine, N-ethyl-m-toluidine, triethanolamine, m-toluidine, diethylenetriamine, pyridine, phenylmorpholine, piperidine, N,N-bis(hydroxyethyl)aniline, and diethanolaniline, N,N-substituted-p-toluidines, and amines such as 4-(N,N-substituted amino)benzaldehyde. When the radical polymerizable resin composition of the present invention contains the curing accelerator (G), the amount thereof is preferably 0.01 to 10 parts by mass, more preferably 0.05 to 5 parts by mass, and further preferably 0.1 to 3 parts by mass, relative to 100 parts by mass of the radical polymerizable compound (A).

[0074] <Fiber (H)> The radical polymerizable composition of the present invention may contain fibers as necessary. Specific examples of fibers that can be used in the present invention include glass fibers, carbon fibers, vinylon fibers, nylon fibers, aramid fibers, polyolefin fibers, acrylic fibers, polyester fibers such as polyethylene terephthalate fibers, cellulose fibers, metal fibers such as steel fibers, and ceramic fibers such as alumina fibers. Among them, for example, polyolefin fibers can be used as a thixotropic agent. A thixotropic agent (a thixotropic agent) is a compounded agent for the purpose of imparting thixotropy.

[0075] Polyolefin fibers currently available on the market include polyethylene-based products with trade names such as Chemivest (registered trademark) FDSS-2 (average fiber length 0.6 mm), Chemivest (registered trademark) FDSS-5 (average fiber length 0.1 mm), Chemivest (registered trademark) FDSS-25 (average fiber length 0.6 mm, hydrophilized product), and Chemivest (registered trademark) FDSS-50 (average fiber length 0.1 mm, hydrophilized product) (all manufactured by Mitsui Petrochemical Industries, Ltd.).

[0076] The carbon fiber is not particularly limited, and any known carbon fiber can be used. Examples include polyacrylonitrile (PAN) carbon fiber, rayon carbon fiber, pitch carbon fiber, and the like. The carbon fibers may be used alone or in combination of two or more. From the viewpoint of low cost and good mechanical properties, it is preferable to use PAN carbon fiber. Such carbon fibers are commercially available. Carbon fiber reinforced plastic (CFRP) may be used as the carbon fiber.

[0077] The diameter of the carbon fiber is preferably 3 to 15 μm, more preferably 5 to 10 μm. The length of the carbon fiber is usually 5 to 100 mm. In the present invention, the carbon fiber may be cut to 10.0 mm to 100.0 mm, or further 12.5 mm to 50.0 mm before use.

[0078] These fibers are preferably used in the form of a fiber structure, biaxial mesh, or triaxial mesh selected from plain weave, satin weave, nonwoven fabric, mat, roving, chop, knit, braid, and composite structures thereof, etc. For example, the fiber structure can be impregnated with a radical polymerizable composition, and optionally prepolymerized to form a prepreg, before use. As the mesh, for example, a biaxial mesh or a triaxial mesh is used. The length of one side of a square of the biaxial mesh (mesh size) and the length of one side of an equilateral triangle of the triaxial mesh (mesh size) are each preferably 5 mm or more, more preferably 10 to 20 mm. By using a biaxial mesh or a triaxial mesh, a hardening material for preventing spalling of concrete can be obtained that is lightweight and has excellent economic efficiency, workability, and durability. These fibers are preferably used when reinforcing coating film performance such as concrete spalling prevention and FRP waterproofing, or when producing FRP molded products. For applications such as preventing concrete spalling, glass fibers and cellulose fibers, which have excellent transparency among fibers, are preferred because they allow the deterioration state of the base to be visually inspected from the outside.

[0079] The content of such fibers is preferably 0.3 to 200 parts by mass, more preferably 0.5 to 100 parts by mass, and further preferably 1.0 to 50 parts by mass, relative to 100 parts by mass of the radically polymerizable compound (A).

[0080] <Polymerization inhibitor (I)> The radically polymerizable resin composition of the present invention may contain a polymerization inhibitor from the viewpoint of suppressing excessive polymerization of the radically polymerizable compound (A) and controlling the reaction rate. Examples of the polymerization inhibitor include known ones such as hydroquinone, methylhydroquinone, phenothiazine, catechol, and 4-tert-butylcatechol. When the radically polymerizable resin composition contains a polymerization inhibitor (I), the amount thereof is 0.0001 to 10 parts by mass, more preferably 0.001 to 1 part by mass, per 100 parts by mass of the radically polymerizable compound (A).

[0081] <Cure retarder (J)> The radical polymerizable resin composition of the present invention may contain a curing retarder for the purpose of retarding the curing of the radical polymerizable compound (A). Examples of the curing retarder include free radical curing retarders, such as TEMPO derivatives, such as 2,2,6,6-tetramethylpiperidine 1-oxyl free radical (TEMPO), 4-hydroxy-2,2,6,6-tetramethylpiperidine 1-oxyl free radical (4H-TEMPO), and 4-oxo-2,2,6,6-tetramethylpiperidine 1-oxyl free radical (4-Oxo-TEMPO). Among these, 4-hydroxy-2,2,6,6-tetramethylpiperidine 1-oxyl free radical (4H-TEMPO) is preferred from the standpoint of cost and ease of handling. When the radically polymerizable resin composition contains a curing retarder (J), the amount thereof is preferably 0.0001 to 10 parts by mass, more preferably 0.001 to 1 part by mass, based on 100 parts by mass of the radically polymerizable compound (A).

[0082] <Water reducing agent (L)> The radical polymerizable resin composition of the present invention may contain a usable water reducing agent (L) that can impart water reducibility, if necessary. As the water reducing agent, any known water reducing agent used in concrete, such as liquid or powder water reducing agents, AE water reducing agents, high performance water reducing agents, and high performance AE water reducing agents, can be used without limitation. Polycarboxylic acid-based water-reducing agents are capable of suppressing the decrease in fluidity of concrete that accompanies the addition of the above-mentioned swelling aluminosilicate, and are also suitable from the viewpoint of maintaining good fluidity and improving workability. As the water reducing agent, any known water reducing agent used in concrete, such as liquid or powder water reducing agents, AE water reducing agents, high performance water reducing agents, and high performance AE water reducing agents, can be used without any restrictions. Polycarboxylic acid-based water-reducing agents are capable of suppressing the decrease in fluidity of concrete that accompanies the addition of the above-mentioned swelling aluminosilicate, and are also suitable from the viewpoint of maintaining good fluidity and improving workability.

[0083] The water reducing agent is preferably contained in an amount of 0.1 to 3.0% by mass in the radical polymerizable resin composition.

[0084] <Other ingredients> The radical polymerizable resin composition of the present invention may contain components other than the above-mentioned components, so long as they do not significantly impair the strength expression or acid resistance of the cured product. Examples of the components that can be contained include hydraulic inorganic substances such as calcium sulfate and pozzolanic substances, as well as admixtures that can be used in mortar or concrete to impart properties such as setting adjustment, hardening acceleration, hardening retardation, thickening, water retention, defoaming, water repellency, and waterproofing, and admixtures that can be used in mortar or concrete, such as fibers made of materials such as metals, polymers, and carbon, pigments, extenders, foaming agents, and clay minerals such as zeolites. Examples of the components that can be contained include coupling agents, plasticizers, anion fixing components, solvents, polyisocyanate compounds, surfactants, wetting and dispersing agents, waxes, and thixotropic agents.

[0085] [Coupling Agent] The radical polymerizable resin composition of the present invention may contain a coupling agent for the purpose of improving processability, adhesion to a substrate, etc. Examples of the coupling agent include known silane-based coupling agents, titanate-based coupling agents, and aluminum-based coupling agents. Examples of such coupling agents include R 3 -Si(OR 4 Examples of the silane coupling agent include those represented by the formula R 3 Examples of the alkyl group include an aminopropyl group, a glycidyloxy group, a methacryloxy group, an N-phenylaminopropyl group, a mercapto group, and a vinyl group. 4 Examples of the alkyl group include a methyl group and an ethyl group. When the radically polymerizable resin composition contains a coupling agent, the amount thereof is preferably 0.001 to 10 parts by mass relative to 100 parts by mass of the radically polymerizable compound (A).

[0086] [Plasticizer] The radically polymerizable resin composition of the present invention may contain a plasticizer, if necessary. The plasticizer is not particularly limited, and for the purpose of adjusting the physical properties and characteristics, for example, phthalate esters such as dibutyl phthalate, diheptyl phthalate, di(2-ethylhexyl) phthalate, and butyl benzyl phthalate; non-aromatic dibasic acid esters such as dioctyl adipate, dioctyl sebacate, dibutyl sebacate, and isodecyl succinate; aliphatic esters such as butyl oleate and methyl acetyl ricinoleate; polyalkylene glycol esters such as diethylene glycol dibenzoate, triethylene glycol dibenzoate, and pentaerythritol ester; phosphate esters such as tricresyl phosphate and tributyl phosphate; trimellitic acid esters; polystyrenes such as polystyrene and poly-α-methylstyrene; polybutadiene, polybutene, polyisobutylene, butadiene-acrylonitrile, and polychloroprene; chlorinated paraffins; hydrocarbon oils such as alkyl diphenyls and partially hydrogenated terphenyls; and process oils. Examples of the polyether polyols include polyethylene glycol, polypropylene glycol, polytetramethylene glycol, and other polyether polyols, and derivatives in which the hydroxyl groups of these polyether polyols are converted to ester groups, ether groups, and the like; epoxy plasticizers such as epoxidized soybean oil and epoxy benzyl stearate; polyester plasticizers obtained from dibasic acids such as sebacic acid, adipic acid, azelaic acid, and phthalic acid, and dihydric alcohols such as ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, and dipropylene glycol; and vinyl polymers obtained by polymerizing vinyl monomers such as acrylic plasticizers by various methods. Among them, it is preferable to add a polymer plasticizer which is a polymer having a number average molecular weight of 500 to 15,000, since it is possible to adjust the viscosity of the radical polymerizable composition and the mechanical properties such as tensile strength and elongation of the cured product obtained by curing the composition. Moreover, the polymer plasticizer is preferable because it can maintain the initial physical properties for a long period of time compared with the case where a low molecular weight plasticizer which is a plasticizer that does not contain a polymer component in the molecule is used. Although not limited, this polymer plasticizer may or may not have a functional group. The number average molecular weight of the polymer plasticizer is more preferably 800 to 10,000, and even more preferably 1,000 to 8,000. If the number average molecular weight is 500 or more, the plasticizer can be prevented from flowing out over time due to the influence of heat, rainfall, and water, and the initial physical properties can be maintained for a long period of time. If the number average molecular weight is 15,000 or less, the viscosity increase can be prevented, and sufficient workability can be ensured.

[0087] [Anion fixing component] In addition, hydrotalcites or hydrocalumites can be used to immobilize anions such as chloride ions. These hydrotalcites may be natural or synthetic, and may be used regardless of whether they have been surface-treated or have water of crystallization. For example, hydrotalcites represented by the following general formula (R)

[0088] M x Magnesium y ·Al Z CO3(OH) xr+2y+3z-2 mH2O (R)

[0089] (wherein M is an alkali metal or zinc, x is a number from 0 to 6, y is a number from 0 to 6, z is a number from 0.1 to 4, r is the valence of M, and m is the number of water of crystallization (0 to 100). The hydrocalumite may be a natural product or a synthetic product, and may be used regardless of whether it is surface-treated or has water of crystallization. For example, hydrocalumite represented by the following general formula (S) or (T):

[0090] 3CaO Al2O3 CaX2 kH2O (S)

[0091] (X is a monovalent anion, k≦20)

[0092] 3CaO Al2O3 CaY kH2O (T)

[0093] (Y is a divalent anion, k≦20) Examples of the above-mentioned formulas are given below.

[0094] In addition, calumite contains nitrite ions (NO2 - ) is supported, but an example of an anion that can be supported is the nitrate ion (NO3 - ), hydroxide ion (OH - ), oxalate ion (CH3COO - ), carbonate ion (CO3 - ), sulfate ion (SO4 2- ) etc.

[0095] These hydrotalcites or hydrocalumites may be used alone, but can also be used by being mixed into cement paste. When mixed with cement paste, the hydroxide ions (OH - ) or sulfate ions (SO4 2- ) is expected to have various effects on the anion exchange reaction that is a characteristic of calumite. From the viewpoint of maintaining the exchange reaction with the targeted chloride ions, hydrocalumite that supports nitrite ions is preferable.

[0096] 〔solvent〕 The radical polymerizable resin composition of the present invention may contain a solvent if necessary. Examples of the solvent that may be contained include aromatic hydrocarbon solvents such as toluene and xylene; ester solvents such as ethyl acetate, butyl acetate, amyl acetate, and cellosolve acetate; and ketone solvents such as methyl ethyl ketone, methyl isobutyl ketone, and diisobutyl ketone. These solvents may be used during the production of the polymer.

[0097] [Polyisocyanate Compound] The radically polymerizable resin composition of the present invention may contain a polyisocyanate compound, which reacts with the hydroxyl group of the radically polymerizable compound (A) to form a cured coating film. The polyisocyanato compound contains two or more isocyanato groups in the molecule, and the isocyanato groups may be blocked with a blocking agent or the like. Examples of polyisocyanate compounds that are not blocked with a blocking agent include aliphatic diisocyanates such as lysine diisocyanate, hexamethylene diisocyanate, and trimethylhexane diisocyanate; cyclic aliphatic diisocyanates such as hydrogenated xylylene diisocyanate, isophorone diisocyanate, methylcyclohexane-2,4 (or 2,6)-diisocyanate, 4,4'-methylenebis(cyclohexylisocyanate), and 1,3-(isocyanatomethyl)cyclohexane; aromatic diisocyanates such as tolylene diisocyanate, xylylene diisocyanate, and diphenylmethane diisocyanate; and polyisocyanates having three or more valences such as lysine triisocyanate, as well as adducts of each of these polyisocyanates with polyhydric alcohols, low-molecular-weight polyester resins, water, or the like, cyclized polymers of the above-mentioned diisocyanates (for example, isocyanurates), and biuret-type adducts. Among these, the isocyanurate of hexamethylene diisocyanate is preferred. These polyisocyanate compounds may be used alone or in combination of two or more kinds.

[0098] When the radical polymerizable resin composition contains a polyisocyanato compound, the amount thereof is preferably 0.1 to 50 parts by mass, more preferably 1 to 30 parts by mass, and even more preferably 2 to 20 parts by mass, relative to 100 parts by mass of the radical polymerizable compound (A).

[0099] The blocked polyisocyanato compound is a compound obtained by blocking the isocyanato groups of the above polyisocyanato compound with a blocking agent. Examples of blocking agents include phenol-based agents such as phenol, cresol, and xylenol; ε-caprolactam; lactam-based agents such as δ-valerolactam, γ-butyrolactam, and β-propiolactam; alcohol-based agents such as methanol, ethanol, n- or iso-propyl alcohol, n-, iso-, or tert-butyl alcohol, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, propylene glycol monomethyl ether, and benzyl alcohol; oxime-based agents such as formamidoxime, acetaldoxime, acetoxime, methylethylketoxime, diacetylmonoxime, benzophenoneoxime, and cyclohexaneoxime; and active methylene-based agents such as dimethyl malonate, diethyl malonate, ethyl acetoacetate, methyl acetoacetate, and acetylacetone. By mixing the polyisocyanate with the blocking agent, the isocyanato group of the polyisocyanate can be easily blocked.

[0100] When the polyisocyanato compound is an unblocked polyisocyanato compound, a reaction between the radical polymerizable compound (A) in the radical polymerizable resin composition of the present invention and the polyisocyanato compound occurs when they are mixed. Therefore, it is preferable to separate the radical polymerizable compound (A) and the polyisocyanato compound until use and mix the two at the time of use. In addition, a curing catalyst can be used to react the radical polymerizable compound (A) with the polyisocyanate compound. Suitable curing catalysts include, for example, organometallic catalysts such as tin octylate, dibutyltin di(2-ethylhexanoate), dioctyltin di(2-ethylhexanoate), dioctyltin diacetate, dibutyltin dilaurate, dibutyltin oxide, dioctyltin oxide, and lead 2-ethylhexanoate. When the radically polymerizable resin composition contains the above-mentioned amount of the curing catalyst, the amount thereof is preferably 0.01 to 5 parts by mass, more preferably 0.05 to 4 parts by mass, based on 100 parts by mass of the radically polymerizable compound (A).

[0101] [Surfactant] The radical polymerizable resin composition of the present invention may contain a surfactant. The surfactant may be an anionic surfactant, a nonionic surfactant, a cationic surfactant, or an amphoteric surfactant. These surfactants may be used alone or in combination of two or more. Among these surfactants, one or more selected from anionic surfactants and nonionic surfactants are preferred.

[0102] Examples of anionic surfactants include alkyl sulfate salts such as sodium lauryl sulfate and triethanolamine lauryl sulfate; polyoxyethylene alkyl ether sulfate salts such as sodium polyoxyethylene lauryl ether sulfate and triethanolamine polyoxyethylene alkyl ether sulfate; sulfonates such as dodecylbenzenesulfonic acid, sodium dodecylbenzenesulfonate, sodium alkylnaphthalenesulfonate, and sodium dialkylsulfosuccinate; fatty acid salts such as sodium stearate soap, potassium oleate soap, and potassium castor oil soap; naphthalenesulfonic acid formalin condensates, and special polymer systems. Among these, sulfonates are preferred, dialkyl sodium sulfosuccinate is more preferred, and dioctyl sodium sulfosuccinate is even more preferred.

[0103] Examples of nonionic surfactants include polyoxyethylene alkyl ethers such as polyoxylauryl ether, polyoxyethylene cetyl ether, polyoxyethylene stearyl ether, and polyoxyethylene oleyl ether; polyoxyethylene derivatives such as polyoxyethylene distyrenated phenyl ether, polyoxyethylene tribenzyl phenyl ether, and polyoxyethylene polyoxypropylene glycol; polyoxyalkylene alkyl ethers; sorbitan fatty acid esters such as sorbitan monolaurate, sorbitan monopalmitate, and sorbitan monostearate; polyoxyethylene sorbitan fatty acid esters such as polyoxyethylene sorbitan monolaurate, polyoxyethylene sorbitan monolaurate, and polyoxyethylene sorbitan monopalmitate; polyoxyethylene sorbitol fatty acid esters such as polyoxyethylene sorbitan tetraoleate; and glycerin fatty acid esters such as glycerin monostearate and glycerin monooleate. Among these, polyoxyethylene lauryl ether, polyoxyethylene cetyl ether, polyoxyethylene stearyl ether, polyoxyethylene oleyl ether, and polyoxyethylene alkyl ether are preferred. The HLB (Hydrophile-Lipophil Balance) of the nonionic surfactant is preferably 5 to 15, and more preferably 6 to 12.

[0104] When the radical polymerizable resin composition contains a surfactant, the amount thereof is preferably 0.01 to 10 parts by mass, more preferably 0.05 to 7 parts by mass, and even more preferably 0.1 to 5 parts by mass, relative to 100 parts by mass of the radical polymerizable compound (A).

[0105] [Wetting and dispersing agent] The radical polymerizable resin composition of the present invention may contain a wetting and dispersing agent, for example, in order to improve the permeability into a wet or submerged repair site. Examples of wetting and dispersing agents include fluorine-based wetting and dispersing agents and silicone-based wetting and dispersing agents, which may be used alone or in combination of two or more kinds. Commercially available fluorine-based wetting and dispersing agents include Megafac (registered trademark) F176, Megafac (registered trademark) R08 (manufactured by Dainippon Ink and Chemicals, Inc.), PF656, PF6320 (manufactured by OMNOVA), Troysol S-366 (manufactured by Troy Chemical Co., Ltd.), Fluorad FC430 (manufactured by 3M Japan Ltd.), and polysiloxane polymer KP-341 (manufactured by Shin-Etsu Chemical Co., Ltd.). Commercially available silicone-based wetting and dispersing agents include BYK (registered trademark)-322, BYK (registered trademark)-377, BYK (registered trademark)-UV3570, BYK (registered trademark)-330, BYK (registered trademark)-302, BYK (registered trademark)-UV3500, BYK-306 (manufactured by BYK Japan KK), and polysiloxane polymer KP-341 (manufactured by Shin-Etsu Chemical Co., Ltd.).

[0106] The silicone-based wetting and dispersing agent preferably contains a compound represented by the following formula (U). [ka]

[0107] (In the formula, R 5 and R 6 are each independently a hydrocarbon group having 1 to 12 carbon atoms which may contain an aromatic ring, or -(CH2)3O(C2H4O) p (CH2CH(CH3)O) q R' represents an alkyl group having 1 to 12 carbon atoms, n is an integer of 1 to 200, p and q are each an integer, and q / p=0 to 10 is satisfied. In addition, examples of commercially available silicone-based wetting and dispersing agents containing the compound represented by formula (U) include BYK (registered trademark)-302 and BYK (registered trademark)-322 (manufactured by BYK Japan KK). When the radically polymerizable resin composition of the present invention contains a wetting dispersant, the amount thereof is preferably 0.001 to 5 parts by mass, more preferably 0.01 to 2 parts by mass, based on 100 parts by mass of the radically polymerizable compound (A).

[0108] 〔wax〕 The radical polymerizable resin composition of the present invention may contain a wax. Examples of waxes include paraffin waxes and polar waxes, which may be used alone or in combination of two or more kinds. The paraffin waxes may be any known wax having a variety of melting points. The polar waxes may be any wax having both polar and non-polar groups in its structure, and specific examples thereof include NPS (registered trademark)-8070, NPS (registered trademark)-9125 (manufactured by Nippon Seiro Co., Ltd.), Emanone (registered trademark) 3199, and Emanone (registered trademark) 3299 (manufactured by Kao Corporation). When the radical polymerizable resin composition of the present invention contains a wax, the amount of the wax is preferably 0.05 to 4 parts by mass, more preferably 0.1 to 2.0 parts by mass, based on 100 parts by mass of the radical polymerizable compound (A). However, when the radical polymerizable resin composition of the present invention is used in water, it is preferable not to use a wax since there is a risk that the wax will dissolve in the water.

[0109] [Thixotropic Agent] The radical polymerizable resin composition of the present invention may contain a thixotropic agent for the purpose of adjusting the viscosity in order to ensure workability on vertical surfaces and ceiling surfaces. Examples of the thixotropic agent include inorganic thixotropic agents and organic thixotropic agents. Examples of the organic thixotropic agents include hydrogenated castor oil-based, amide-based, oxidized polyethylene-based, vegetable oil polymerized oil-based, surfactant-based, and composite systems using these in combination. Specific examples include DISPARLON (registered trademark) 6900-20X (Kusumoto Chemical Co., Ltd.). In addition, examples of inorganic thixotropic agents include silica and bentonite, and examples of hydrophobic agents include Reolosil (registered trademark) PM-20L (fumed silica manufactured by Tokuyama Corporation) and Aerosil (registered trademark) AEROSIL R-106 (Nippon Aerosil Co., Ltd.), and examples of hydrophilic agents include Aerosil (registered trademark) AEROSIL-200 (Nippon Aerosil Co., Ltd.). From the viewpoint of further improving the thixotropic properties, a thixotropic modifier such as BYK (registered trademark)-R605 or BYK (registered trademark)-R606 (manufactured by BYK Japan Co., Ltd.) may also be suitably used in which hydrophilic calcined silica is added. When the radical polymerizable resin composition of the present invention contains a thixotropic agent, the amount of the thixotropic agent is preferably 0.01 to 10 parts by mass, more preferably 0.1 to 5 parts by mass, based on 100 parts by mass of the radical polymerizable compound (A).

[0110] <Water> The radical polymerizable resin composition of the present invention does not substantially contain water from the viewpoint of obtaining a practical level of strength. That is, when preparing the radical polymerizable resin composition, water is not added as a constituent of the composition. For example, the water content of the radical polymerizable resin composition is preferably less than 0.25 parts by mass, more preferably 0.20 parts by mass or less, further preferably 0.15 parts by mass or less, and most preferably 0.10 parts by mass or less, relative to 100 parts by mass of the radical polymerizable compound (A).

[0111] <Method for producing radically polymerizable resin composition> The method for producing the radical polymerizable resin composition of the present invention is not particularly limited, and can be a method known in the art. For example, the radical polymerizable resin composition can be produced by mixing the radical polymerizable compound (A) with the metal-containing compound (E) as necessary, and further mixing the radical polymerization initiator (C), the aggregate containing cement (D), and the expansive material (B). One embodiment of the method for producing the radical polymerizable resin composition of the present invention includes a step (S1) of mixing a radical polymerizable compound (A) with a metal-containing compound (E) as necessary to obtain a resin product, a step (S2) of mixing the obtained resin product with a radical polymerization initiator (C) to obtain a curable resin product, and a step (S3) of mixing the obtained curable resin product with a cement-containing aggregate (D) and an expandable material (B) to obtain a radical polymerizable resin composition.

[0112] In the step (S1) of obtaining the resin product (sometimes simply referred to as "step (S1)"), in addition to mixing the metal-containing compound (E) with the radically polymerizable compound (A), a polymerization inhibitor (I), a curing retarder (J), a thiol compound (F), etc. may also be mixed, if necessary. In the step (S3) (sometimes simply referred to as "step (S3)") of obtaining a radical polymerizable resin composition, in addition to mixing the cement-containing aggregate (D) and the expansive material (B) with the curable resin product obtained in the step (S2) (sometimes simply referred to as "step (S2)") of obtaining a curable resin product, a water-reducing agent (L) and / or fibers (H) may be further mixed, if necessary. Specific examples of the aggregate (D) that can be used include high-early-strength Portland cement, calcium carbonate TM-2, perlite FL-0, hard light B-04, Enshu No. 5.5 silica sand, N50 silica sand, N40 silica sand, and N90 silica sand.

[0113] The radical polymerizable resin composition thus produced can be cured at room temperature and has excellent workability, early strength development, and curing properties. Since it contains the expanding agent (B), the shrinkage rate during curing is small, and depending on the conditions, the expansion rate of the cured product can be made larger than 0.

[0114] <Cured product of radically polymerizable resin composition> The cured product of the radical polymerizable resin composition of the present invention can be obtained by curing the above-mentioned radical polymerizable resin composition.

[0115] [Method of curing radically polymerizable resin composition] When the radical polymerizable resin composition of the present invention contains a thermal radical polymerization initiator (C1), an example of a method for curing the radical polymerizable resin composition of the present invention is a method for curing the radical polymerizable resin composition of the present invention by applying the radical polymerizable resin composition of the present invention to the surface of a substrate and curing it at room temperature. For example, the radical polymerizable resin composition of the present invention is used as a cross-section repair material for inorganic structures. Since the radical polymerizable resin composition of the present invention contains an expansion agent (B), the obtained cured product does not shrink significantly even after a certain period of time, as in the past. Examples of materials for the substrate include concrete, asphalt concrete, mortar, brick, wood, and metal, as well as thermosetting resins such as phenolic resin, epoxy resin, melamine resin, urea resin, unsaturated polyester resin, vinyl ester resin, alkyd resin, polyurethane, and polyimide; and thermoplastic resins such as polyethylene, polypropylene, polyvinyl chloride, polystyrene, polyvinyl acetate, polyurethane, Teflon (registered trademark), ABS resin, AS resin, and acrylic resin.

[0116] When the radical polymerizable resin composition of the present invention contains a photoradical polymerization initiator (C2), the timing of photocuring may be, for example, a method in which the radical polymerizable resin composition is applied to a substrate and then photocured, or a method in which a sheet is prepared by prepolymerizing the radical polymerizable resin composition in advance (also called B-stage or prepreg), and the sheet is attached to a substrate and then photocured.

[0117] The light source may be any light source having a spectral distribution in the photosensitive wavelength range of the photoradical polymerization initiator (C2), and may be, for example, sunlight, an ultraviolet lamp, a near-infrared lamp, a sodium lamp, a halogen lamp, a fluorescent lamp, a metal halide lamp, an LED, or the like. In addition, two or more types of photoradical polymerization initiators (C2) may be used in combination, and a wavelength cut filter may be used as the light source, or a specific wavelength of an LED may be used to selectively use the wavelengths required for preliminary polymerization and main polymerization. The wavelengths used for preliminary polymerization are preferably long wavelengths with low energy levels, and the degree of polymerization is easily controlled by using near-infrared light in particular. In the present invention, ultraviolet light (ultraviolet rays) refers to light rays in the wavelength range of 280 to 380 nm, visible light (visible rays) refers to light in the wavelength range of 380 to 780 nm, and near-infrared light (near-infrared rays) refers to light in the wavelength range of 780 to 1200 nm. The irradiation time of the lamp required for preliminary polymerization cannot be generally specified because it is affected by the effective wavelength range, output, irradiation distance, thickness of the composition, etc. of the light source, but it is sufficient to irradiate for, for example, 0.01 hours or more, preferably 0.05 hours or more. EXAMPLES

[0118] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples in any way.

[0119] <How to measure cure shrinkage> The post-curing shrinkage and expansion rates (change rate: negative number is shrinkage rate, positive number is expansion rate) of the cured product of the radical polymerizable resin composition of the present invention were measured in accordance with Japanese Standard JIS A 1129-3 (dial gauge method). The molding (cured product) was prepared by referring to Appendix A of Japanese Standard JIS A 1129. A mold for a specimen of 40×40×160 mm specified in Japanese Standard JIS R 5201 was used. The cured product specimen was molded according to the method for preparing a specimen for strength test specified in JIS R 5201, 10. After molding, the specimen was left to stand (cured) in a room at a temperature of 23° C.±2° C. and a humidity of 50% while still in the mold, and was demolded about 24 hours after molding. Then, the measurement was started using the equipment specified in JIS A 1129-3, 3, under the conditions specified in JIS A 1129-3, 4.3 (time is set to 0).

[0120] Change (negative number: contraction amount, positive number: expansion amount) = long side length over time - long side length at start (0 o'clock) (160 mm) (1)

[0121] Rate of change (negative number: contraction rate, positive number: expansion rate) = amount of change / length of long side at start (0 o'clock) (160 mm) (2)

[0122] The raw materials used in the production of each radically polymerizable resin composition in the examples and comparative examples are as follows.

[0123] <Radically polymerizable compound (A)> Radical polymerizable compound (A-1) Unsaturated polyester resin Rigolac (registered trademark), Showa Denko K.K., SR-110N (styrene content 40% by mass)

[0124] (Synthesis Example 1) "Synthesis of radically polymerizable compound (A-2)" A 1L four-necked separable flask equipped with a stirrer, reflux condenser, gas inlet tube and thermometer was charged with 150.4g of AER-2603 (Asahi Kasei Corporation, bisphenol A type epoxy resin: epoxy equivalent 189), 188.4g of SR-16H (Sakamoto Yakuhin Kogyo Co., Ltd., 1,6-hexanediol diglycidyl ether), 0.255g of methyl hydroquinone, and 1.5g of DMP-30 (Tokyo Kasei Kogyo Co., Ltd., 2,4,6-tris(dimethylaminomethyl)phenol), and the temperature was raised to 110°C. After the temperature was raised to 110°C, 172g of methacrylic acid (Mitsubishi Rayon Co., Ltd.) was added dropwise over about 30 minutes, and the reaction was continued for about 4 hours. When the acid value reached 10mgKOH / g, the reaction was terminated, and a vinyl ester compound was obtained. Next, 256.3 g of dicyclopentenyloxyethyl methacrylate (Hitachi Chemical Co., Ltd., FA-512MT) and 85.4 g of dicyclopentanyl methacrylate (Hitachi Chemical Co., Ltd., FA-513M) were added as radically polymerizable unsaturated monomers to obtain a non-styrene type radically polymerizable compound (A-2) with a viscosity of 280 mPa s at 25°C and an ester compound component ratio of 60 mass%.

[0125] <Expansion material (B)> B-1: Pacific Hyperexpan-K (for structural use) made by Pacific Materials as a quicklime-based expansive material B-2: Taiheiyo N-EX (high-early hardening expansive material) made by Taiheiyo Materials as a quicklime-based expansive material B-3: As an ettringite-based expanding agent, Denka CSA #10 manufactured by Denka B-4: Denka Power CSA Type S, manufactured by Denka, as a quicklime-ettringite composite expanding material

[0126] <Radical polymerization initiator (C)> As the thermal radical polymerization initiator, (C-1) cumene hydroperoxide (CHP), Percumyl (registered trademark) H-80 manufactured by NOF Corporation, was used. As the thermal radical polymerization initiator, (C-2) diisopropylbenzene hydroperoxide, Percumyl (registered trademark) P manufactured by NOF Corporation, was used. As a thermal radical polymerization initiator, (C-3) benzoyl peroxide, NOF Corporation, Niper (registered trademark) NS was used. As the thermal radical polymerization initiator, (C-4) methyl ethyl ketone peroxide, Permec (registered trademark) N manufactured by NOF Corporation, was used.

[0127] <Aggregate (D)> Aggregate (DI): High early strength portland cement Calcium carbonate TM-2 Perlite FL-0 Hard Light B-04 Enshu No. 5.5 silica sand N50 silica sand N40 silica sand Aggregate (D-II): Bond P mortar aggregate, manufactured by Konishi Co., Ltd. (contains high-early-strength Portland cement)

[0128] <Metal-containing compounds (E)> As the metal soap, (E-1) cobalt octylate (manufactured by Toei Kako Co., Ltd., cobalt hexoate, cobalt content in the total amount of the product: 8 mass %, molecular weight: 345.34) was used. As the metal soap, (E-2) manganese octylate (manganese hexoate, manufactured by Toei Kako Co., Ltd., manganese content in the total amount of the product is 8 mass %, molecular weight is 341.35) was used.

[0129] <Thiol Compound (F)> As the secondary thiol compound (F-1), KarenzMT (registered trademark) BD1 (1,4-bis(3-mercaptobutyryloxy)butane, molecular weight 299.43), a bifunctional secondary thiol manufactured by Showa Denko KK, was used.

[0130] <Curing accelerator (G)> As the curing accelerator (G-1), dimethylaniline (DMA, manufactured by Tokyo Chemical Industry Co., Ltd.) was used.

[0131] <Fiber (H)> Chemivest (registered trademark) FDSS-5 Polyolefin hyperbranched fiber manufactured by Mitsui Fine Chemicals Co., Ltd.

[0132] <Polymerization inhibitor (I)> As the polymerization inhibitor (I-1), tertiary butyl catechol was used. As the polymerization inhibitor (I-2), dibutylhydroxytoluene was used.

[0133] <Cure retarder (J)> 4-H-TEMPO was used.

[0134] <Epoxy resin> Base material: Epoxy resin, Bond E208W, manufactured by Konishi Hardener: Epoxy resin hardener, Bond E208W, manufactured by Konishi Co., Ltd.

[0135] Example 1 "Preparation of radically polymerizable resin composition" (1) Process (S1): The radical polymerizable compound (A-2) obtained in Synthesis Example 1 was thoroughly mixed with the metal-containing compound (E), the thiol compound (F), the polymerization inhibitor (I), and the curing retarder (J) in the amounts shown in Table 1 to prepare a resin product. (2) Process (S2): The resin product obtained in the step (S1) was mixed with the radical polymerization initiator (C) in the blending amount shown in Table 1 to prepare a curable resin product. (3) Process (S3): The curable resin product obtained in step (S2) was thoroughly mixed with the expandable material (B), aggregate (D), and fiber (H) in the amounts of each component shown in Table 1 to obtain the radical polymerizable resin composition of this example.

[0136] The mixing conditions in each step were as follows. Mixer: HOMOGENIZING DISPER Model 2.5 (Primix) Agitation speed: 3000-5000 rpm Temperature: 25℃

[0137] "Preparation of cured product of radically polymerizable resin composition" The obtained radical polymerizable resin composition was poured into a 40×40×160 mm mold, and left to stand (cure) in a room at a temperature of 23° C.±2° C. and a humidity of 50% to harden, and then demolded about 24 hours after molding. A hardened product of the radical polymerizable resin composition of this example was obtained.

[0138] "Evaluation of shrinkage and expansion of cured materials" The cured product of the obtained radical polymerizable resin composition was evaluated by the above-mentioned evaluation methods, and the results are shown in FIG.

[0139] "Evaluation of fluidity of resin composition" The flowability of the resin composition was evaluated using an Ultra Point Gun sold by PCOCOX Japan Sales Co., Ltd. The subject to be evaluated is the radical polymerizable resin composition after mixing in step (S3). 200 g of the radical polymerizable resin composition is loaded into the ultra-point gun, and a rod is set in place according to a prescribed procedure. The trigger is then pulled, and the amount of the radical polymerizable resin composition coming out of the nozzle tip is used as an indicator. When the radical polymerizable resin composition came out, it was evaluated as "Good", and when the radical polymerizable resin composition did not come out, it was evaluated as "Poor". When the radical polymerizable resin composition mixed in step (S3) separated and only the resin came out, it was evaluated as "Good". The results are shown in Table 1.

[0140] (Examples 2 to 13, 15 to 20, Comparative Examples 1 to 6, 10 to 15) Radical polymerizable resin compositions were obtained in the same manner as in Example 1, except that the components and amounts thereof shown in Table 1 were used. Cured products of the radical polymerizable resin compositions were also prepared in the same manner as in Example 1. The shrinkage and expansion properties of the resulting cured products were evaluated in the same manner as in Example 1. The results are shown in Figures 1 to 2, 6 to 9, 10 and 11.

[0141] (Reference example 1) A radical polymerizable resin composition was obtained in the same manner as in Example 1, except that in step (S3), 10 parts by mass of water was mixed with 100 parts by mass of the curable resin product obtained in step (S2). A cured product of the radical polymerizable resin composition was produced in the same manner as in Example 1. The contraction and expansion properties of the cured product were evaluated in the same manner as in Example 1. The results are shown in FIG.

[0142] (Comparative Examples 7 and 8) Instead of the radical polymerizable composition of Example 1, an epoxy resin composition was obtained by using an aggregate (D-II) and an epoxy resin shown in Table 2. A cured product of the epoxy resin composition was produced by the following method. The shrinkage and expansion properties of each of the obtained cured products were evaluated by the same method as in Example 1. The results are shown in Figure 3.

[0143] (Example 14 and Comparative Example 9) Radical polymerizable resin compositions were obtained in the same manner as in Example 1, except that the components and amounts thereof shown in Table 2 were used. Cured products of the radical polymerizable resin compositions were also prepared in the same manner as in Example 1. The shrinkage and expansion properties of the resulting cured products were evaluated in the same manner as in Example 1. The results are shown in FIG.

[0144] "Preparation of cured epoxy resin composition" After thoroughly mixing the epoxy resin base and hardener, aggregate (D-II) and high-early-strength Portland cement were mixed, and the mixture was poured into a 40 x 40 x 160 mm formwork, left to stand (cure) in a room at a temperature of 23°C ± 2°C and humidity of 50% to harden, and demolded about 24 hours after molding. A hardened product of the epoxy resin composition of this comparative example was obtained.

[0145] [Table 1]

[0146] The meanings of the symbols for each component in Table 1 are as follows: A-1 Rigolac (registered trademark) SR-110N E-1 Cobalt octylate I-1 Tertiary butyl catechol I-2 Dibutylhydroxytoluene J-1 4H-TEMPO G-1 Dimethylaniline C-1 Parkmill (registered trademark) H-80 C-2 Parkmil (registered trademark) P C-3 Niper (registered trademark) NS C-4 Permec (registered trademark) N B-1 Pacific Hyper Expansion K (Structural) B-2 Pacific N-EX (high-early hardening expansive material) B-3 Denka CSA #10 B-4 Denka Power CSA Type S d-1 High early strength Portland cement d-2 Calcium carbonate TM-2 d-3 Perlite FL-0 d-4 Hard Light B-04 d-5 Enshu No. 5.5 silica sand d-6 N90 Silica sand d-7 N50 Silica sand d-8 N40 Silica sand d-9 N70 Silica sand

[0147] [Table 2]

[0148] [Table 3]

[0149] FIG. 1 is a graph showing the results of Examples 1 to 4 and Comparative Example 1. For the radical polymerizable resin composition of Comparative Example 1, which does not contain an expanding agent (B), volumetric shrinkage of the cured product was observed. In contrast, for the radical polymerizable resin compositions of Examples 1 to 3, which contain an expanding agent (B), volumetric expansion of the cured product was observed. Furthermore, for the radical polymerizable resin composition of Example 4, volumetric shrinkage was observed within about 0.5 hours from the start of curing, but volumetric expansion was observed thereafter.

[0150] Figure 2 is a graph showing the results of Example 5 and Comparative Example 2. For comparison, Example 1 and Comparative Example 1 in Figure 1 are also shown. From the results in Figure 2, it was found that the effect of adding the expanding material (B) of the present invention does not depend on the type of radical polymerization initiator.

[0151] Fig. 3 is a graph showing the results of Comparative Example 7 and Comparative Example 8. The epoxy resin compositions of Comparative Example 7 and Comparative Example 8 do not contain a radical polymerization initiator (C). In Comparative Example 8, which contained an expanding material (B), the volume expansion effect as in Example 1 was not observed. That is, in a system without a radical polymerization initiator (C), no expansion effect was observed even when an expanding material (B) was contained.

[0152] 4 is a graph showing the results of Example 9 and Comparative Example 14. Even when aggregate (D-II) different from aggregate (DI) was used, a volume expansion effect similar to that of Example 1 was observed in Example 9. FIG. 5 is a graph showing the results of Example 1 and Reference Example 1. A test was carried out in a state where 10 parts by mass of water was intentionally mixed with 100 parts by mass of the resin product. It can be seen that when water was mixed, the initial expansion effect was significantly greater than when water was not mixed. Note that Reference Example 1 is a test example in which water was added without regard for practicality in order to demonstrate the effect of Example 1. It is expected that the strength of the cured product obtained in Reference Example 1 will be significantly reduced, and that the balance of various performances (water resistance, resistance to salt damage, etc.) will be lost.

[0153] FIG. 6 is a graph showing the results of Example 6 and Comparative Example 3. Example 6 and Comparative Example 3 do not contain a thiol compound (F) or a hardening retarder (J-1). An expansion effect was confirmed in Example 6, which contained an expansion agent, but an expansion effect was not confirmed in Comparative Example 3, which did not contain an expansion agent. Therefore, it was found that the thiol compound (F) and the hardening retarder (J-1) did not react with the expansion agent.

[0154] FIG. 7 is a graph showing the results of Example 7 and Comparative Example 4. Example 7 and Comparative Example 4 do not contain a metal-containing compound (E) or a thiol compound (F). In addition, they contain a curing accelerator (G), but the type of polymerization inhibitor (I) is different. An expansion effect was confirmed in Example 7, which contained an expansion agent, while no expansion effect was confirmed in Comparative Example 4, which did not contain an expansion agent. Therefore, it was found that the metal-containing compound (E) did not react with the expansion agent, and that this was not dependent on the type of polymerization inhibitor (I) or the presence or absence of the curing accelerator (G).

[0155] FIG. 8 is a graph showing the results of Example 8 and Comparative Example 5. Example 8 and Comparative Example 5 have different radical polymerizable compounds (A) and different types of metal-containing compounds (E). The radical polymerization initiator (C) is also different from the others. Example 8, which contains an expansion agent, has a clear expansion effect compared to Comparative Example 5, which does not contain an expansion agent. Therefore, it was found that the expansion effect can be achieved regardless of the types of radical polymerizable compounds (A) and metal-containing compounds (E).

[0156] Fig. 9 is a graph showing the results of Examples 9 to 13. Examples 9 to 13 are obtained by increasing or decreasing the amount of the expanding agent added compared to Example 1. Although the expansion effect differs depending on the amount of the expanding agent, it was found that the expansion effect is greater when the amount of the expanding agent is greater.

[0157] Fig. 10 is a graph showing the results of Examples 1 and 15, and Comparative Examples 10 to 15. Fig. 11 is a graph showing the results of Examples 1 and 16 to 20. In Examples 15 to 20 and Comparative Examples 10 to 15, the total amount of aggregate (D) was increased or decreased compared to Example 1. In Examples 15 to 20, a volume expansion effect was observed similarly to Example 1, but in Comparative Examples 10 to 15, no volume expansion effect was observed.

[0158] The results of the fluidity evaluation using an ultra-point gun are shown at the bottom of Tables 1 and 2. In Example 13 and Comparative Examples 6, 7, and 8, the radical polymerizable resin composition did not come out even when the nozzle of the ultra-point gun was pulled. In Example 14 and Comparative Example 9, only the radical polymerizable compound (A) was extruded when the nozzle of the ultra-point gun was pulled. In Example 13, the amount of expansive agent added was extremely large, which is believed to have caused the fluidity of the radical polymerizable resin composition to deteriorate significantly. In Comparative Example 6, the early-strength Portland cement in Example 1 was omitted and replaced with early-strength Portland cement of aggregate (DI). As a result, it is believed that the fluidity of the system that does not contain early-strength Portland cement deteriorated. Furthermore, in Comparative Examples 7 and 8, the epoxy resin base agent, the curing agent, and the aggregate (D-II) were mixed, but it is believed that the fluidity of the epoxy resin composition was too poor. Comparative Example 9 and Example 14 used aggregate (D-II), and like Comparative Examples 7 and 8, had almost no fluidity regardless of the presence or absence of an expansion agent. However, unlike the base agent and hardener of the epoxy resin, it is believed that the radical polymerizable compound (A) was unable to withstand the nozzle pressure of the ultra-point gun, and only the radical polymerizable compound (A) was pushed out.

[0159] The expansion and shrinkage rates (change rate: negative number is shrinkage rate, positive number is expansion rate) of the present invention were measured by leaving the molded product at rest (curing) in a room at a temperature of 23°C ± 2°C and humidity of 50%, demolding it after about 24 hours, and setting the time to 0, under the conditions shown in 4.3 of JIS A 1129-3. That is, the conditions during the test period were a temperature of 20 ± 2°C and a relative humidity of (60 ± 5)%. Under these conditions, it was confirmed that the radical polymerizable resin compositions of Examples 1 to 4, which contain an expanding agent (B), exhibited volume expansion even without adding water to the reaction system. In particular, it was found that Examples 1 to 3, which contain an expanding agent having a quicklime component, had a higher expansion rate than Example 4. It was also found that the radical polymerization initiator (C) is an essential component.

[0160] The results of the present invention show that by adjusting the optimum blending amounts of the resin component, cement component, radical polymerization initiator, expansive agent, etc., it is possible to prepare, for example, a composition in which the volume change rate of the hardened product after a certain period of time is close to zero.

Claims

1. The composition contains a radical polymerizable compound (A), an expanding material (B), a radical polymerization initiator (C), and an aggregate (D), The aggregate (D) contains cement, The amount of the aggregate (D) is 330 parts by mass to 800 parts by mass relative to 100 parts by mass of the radical polymerizable compound (A). A radical polymerizable resin composition comprising:

2. The radical polymerizable resin composition according to claim 1, wherein the radical polymerizable compound (A) comprises a vinyl ester resin and a radical polymerizable unsaturated monomer.

3. 3. The radical polymerizable resin composition according to claim 1, wherein the expanding material (B) comprises at least one selected from the group consisting of quicklime and calcium sulfoaluminate.

4. The radical polymerizable resin composition according to any one of claims 1 to 3, wherein the radical polymerization initiator (C) is a hydroperoxide.

5. The radical polymerizable resin composition according to any one of claims 1 to 4, further comprising a metal-containing compound (E) and a thiol compound (F).

6. The radical polymerizable resin composition according to any one of claims 1 to 5, wherein the expanding material (B) is 0.3 parts by mass to 30 parts by mass relative to 100 parts by mass of the radical polymerizable compound (A).

7. The radical polymerizable resin composition according to any one of claims 1 to 6, wherein the radical polymerization initiator (C) is 0.1 parts by mass to 10 parts by mass relative to 100 parts by mass of the radical polymerizable compound (A).

8. A cured product of the radical polymerizable resin composition according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Ultralow-shrinkage composite resin and preparation method thereof

    CN106420366A

  • Method for repairing cracks on external wall of civil buildings

    CN109653523A

  • Production of fiber-reinforced inorganic form

    JP1993024898A

  • Low-shrinkage unsaturated polyester resin composition

    JP1993222282A

  • Production of low-shrinkage unsaturated polyester resin composition

    JP1999315198A